Investigating Service Quality Perceptions of consumers at Consolidated Store Holdings (CSH) stores in Johannesburg - Pestana, Lucia (The IIE, 2020)
Service quality, customer satisfaction and consumer behaviour have become the primary focus of service organizations in todays customer era. Service Quality is viewed as the output for the service delivery system. The definition of service quality is threefold. Physical quality is viewed as all of the tangible aspects of services offered. Interactive quality makes use of the nature of services in an interactive way, which links the flow between a customer and service provider. Corporate quality is the image of the service provider in the eyes of its customers (Lehtinen & Lehtinen, 1982). The purpose of this research study was to investigate service quality perceptions of consumers at Consolidated Store Holdings (CSH) stores in Johannesburg. The SERVQUAL questionnaire was used as an instrument to measure consumers’ expectations and perceptions according to tangibles and reliability. The fifteen consumers that participated in this study were selected from a CSH store in Johannesburg by use of convenience sampling. Descriptive statistics was used in this study. The study revealed that expectations were higher than perceptions. Both dimensions, tangibles and reliability, scored a negative result which denotes the need for improvement. The negative gap score found was indicative of dissatisfied consumers and that service quality exists in CSH. Conclusions and recommendations were made from the findings of the study.
Keywords: Service quality; Perceptions; Consumers; Johannesburg